Mechanical response of nickel-based anodes in solid oxide fuel cells during carbon deposition using reaction molecular dynamics. (October 2020) - Haibin, Lu; Iqbal, Taosif; Shuzhi, Zhang; Xiongwen, Zhang; Guojun, Li; Di, Zhang
Abstract: Carbon deposition of solid oxide fuel cell (SOFC) anode is a key factor to understand the risk of structural cracking due to mechanical stress. In this study, Grand Canonical Monte Carlo (GCMC) was used under ReaxFF to construct the corresponding carbon deposition model and migration law of carbon atoms. The law of heat generation, diffusion coefficient of volume expansion and mechanical behavior of the nickel carbide composition in the simulation are close to the experimental and theoretically results, which validates the model built by ReaxFF. During analysis, the change in structural characteristics and mechanical properties of the anode caused by the carbon deposition were observed. The variation in volume of carbon deposition during diffusion process was detected, and the structure of the carbon deposition process was studied by combining ohmic loss and radial distribution function (RDF). Influence of carbon deposition on the mechanical properties of the uniaxial tensile process using different models was compared and the behavior of carbon content, expansion/compression rate, poison ratio and nickel carbide formation was obtained. The relationship between Young's modulus and carbon deposition of mechanical properties such as yield stress is clarified.